FEATURES OF THE CLINICAL COURCE OF ARTERIAL HYPERTENSION IN ELDERLY PATIENTS - Almasbek Ayazhan Almasbekovna; Akhmad Nurgulim Sagidullovna (Reviews of Modern Science, 2022)
In this article, we will first consider the anatomy, prevalence, treatment and control of hypertension in the elderly, emphasizing modern definitions of clinical practice recommendations and their importance for the detection of hypertension in the elderl